2012
DOI: 10.1111/j.1745-4549.2012.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

USING PULSED ELECTRIC FIELD FOR IMPROVEMENT OF COMPONENTS EXTRACTION OF SAFFRON (CROCUS SATIVUS ) STIGMA AND ITS POMACE

Abstract: High‐voltage pulsed electric field (PEF) is a promising technology in food processing such as pasteurization, compression and extraction, etc. The present work was devoted to investigation of the effect of PEFs on saffron major components extraction. Major components are color (crocin), flavor (safranal) and taste (picrocrocin). Experiments temperature was fixed at 25C. It has been shown that PEF caused an increase of 14.1% in color, 15.5% in bitterness and 10.2% in taste by voltage of 5 kV, pulse number of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Zderic et al (2013) reported a 7% additional recovery of polysaccharides from cornflowers with an optimal PEF (30 kV/cm, 6 μs) processing. In a different study, Pourzaki et al (2013) measured the effect of PEF (5 kV/cm) on the recovery of the compounds responsible for color, aroma, and flavor of saffron. They have found a substantial rise in the extraction of crocin, safranal, and picrocrocin from the skin of saffron through PEF processing.…”
Section: Results: Recovery Of Biomoleculesmentioning
confidence: 99%
“…Zderic et al (2013) reported a 7% additional recovery of polysaccharides from cornflowers with an optimal PEF (30 kV/cm, 6 μs) processing. In a different study, Pourzaki et al (2013) measured the effect of PEF (5 kV/cm) on the recovery of the compounds responsible for color, aroma, and flavor of saffron. They have found a substantial rise in the extraction of crocin, safranal, and picrocrocin from the skin of saffron through PEF processing.…”
Section: Results: Recovery Of Biomoleculesmentioning
confidence: 99%
“…Pulsed electric field (PEF) has been also used as an alternative means of extraction for saffron apocarotenoids by Pourzaki and co‐workers . High‐voltage pulses cause rupture of cell membranes enhancing solvent permeability .…”
Section: Analysis Of Saffron Apocarotenoidsmentioning
confidence: 99%
“…High‐voltage pulses cause rupture of cell membranes enhancing solvent permeability . The authors suggested that increase in the field strength, pulse number and width enhance recovery of saffron apocarotenoids. The best combination of these conditions was found to be 5 kV, 35 and 100 μs, respectively.…”
Section: Analysis Of Saffron Apocarotenoidsmentioning
confidence: 99%
“…The effect of PEF on extraction of major components from saffron (Crocus sativus) was studied [75]. The extracted components included crocin (color), safranal (flavor), and picrocrocin (taste).…”
Section: Herbsmentioning
confidence: 99%